2020
DOI: 10.1101/2020.12.07.414060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial organization of the transcriptome in individual neurons

Abstract: Neurons are highly polarized cells with complex neurite morphology. Spatial organization and local translation of RNAs in dendrites and axons play an important role in many neuronal functions. Here we performed super-resolution spatial profiling of RNAs inside individual neurons at the genome scale using multiplexed error-robust fluorescence in situ hybridization (MERFISH), and mapped the spatial organization of up to ∼4,200 RNA species (genes) across multiple length scales, ranging from sub-micrometer to mill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…A wide array of ribosome-associated chaperones are vital for nascent chain homeostasis 4,5,[81][82][83] and the degree to which they choreograph assembly steps is yet to be elucidated. Furthermore, because interface size alone does not fully explain the range of affinities observed in a growing number of complexes [46][47][48][49] , it will be exciting to see whether binding affinity plays a role in colocalising mRNA molecules in eukaryotic cells 13,14,19,21,84,85 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A wide array of ribosome-associated chaperones are vital for nascent chain homeostasis 4,5,[81][82][83] and the degree to which they choreograph assembly steps is yet to be elucidated. Furthermore, because interface size alone does not fully explain the range of affinities observed in a growing number of complexes [46][47][48][49] , it will be exciting to see whether binding affinity plays a role in colocalising mRNA molecules in eukaryotic cells 13,14,19,21,84,85 .…”
Section: Discussionmentioning
confidence: 99%
“…This process is highly effective because it takes advantage of the fact that homomeric subunits are identical; hence nascent chains are essentially colocalised by the nature of their synthesis. On the other hand, heteromers, products of distinct genes that stably interact, can only employ the trans mode of assembly in eukaryotes, providing mechanisms that colocalise their transcripts exist [19][20][21] . Although .…”
mentioning
confidence: 99%
“…Lastly, it remains unclear how RNA editing may play out across distinct cellular compartments and locations. Recent work has found discrete gene expression differences across synapses, dendrites, axons and neuronal bodies 43,44 , and RNA editing may represent a driver of activity-induced RNA localization 1,2,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MERFISH's robust experimental design requires no intermediate steps that could cause bias in transcript detection, such as enzymatic amplification. This gives MERFISH an unparalleled target detection efficiency of 95 percent in cell culture [9] and 70 percent in tissue [10].…”
Section: Zeiss Primostarmentioning
confidence: 99%
“…More recently, in a 2020 preprint, Wang et al used MER-FISH to conduct quantitative, high-resolution spatial profiling of ∼4,200 RNA species within mouse hippocampal neurons to MERFISH Method form a cell atlas of the distinct transcriptomic regions inside individual neurons [10]. The authors detected approximately 11,000 RNA molecules per cell and found that cell bodies, axons, dendrites, and even smaller dendritic regions, had their own distinct transcriptional profiles.…”
Section: Zeiss Primostarmentioning
confidence: 99%